Synthesis and Photochemical Properties of Manganese(I) Tricarbonyl Diimine Complexes Bound to Tetrazolato Ligands. Issue 3 (15th January 2020) - Stout, Matthew J.; Stefan, Alessandra; Skelton, Brian W.; Sobolev, Alexandre N.; Massi, Massimiliano; Hochkoeppler, Alejandro; Stagni, Stefano; Simpson, Peter V.
Abstract : Ten manganese(I) tricarbonyl diimine complexes bound to variably functionalised 5‐aryl‐tetrazolato ligands were prepared, and their photochemical properties were investigated. Upon exposure to light at 365 nm, each complex decomposed to its free diimine and tetrazolato ligands, simultaneously dissociating three CO ligands, as evidenced by changes in the IR spectra of the irradiated complexes over time. The anti‐bacterial properties of one of these complexes were tested against Escherichia coli . While the complex displayed no effect on the bacterial growth in the dark, pre‐irradiated solutions inhibited bacterial growth. Comparative studies revealed that the antibacterial properties originate from the presence of free 1, 10‐phenanthroline. Abstract : Tricarbonyl manganese(I) diimine tetrazolato complexes are photochemically active, undergoing ligand release upon irradiation to the lower metal‐to‐ligand charge transfer manifold. The liberated diimine ligands can be exploited to inhibit Escherichia coli growth.